Baja Cente the first training center during the Algerian revolution 1957-1958 - hamri, Issa (The Algerian Historical Journal, 2026)
The revolution attached great importance to the military training that was approved by the Soumam Conference as an effective and essential element, which witnessed a gradual development and continued until independence. Therefore, the leadership of the revolution with its executive body represented by the Coordination and Execution Committee decided to establish centers on the eastern borders for the emergency training of the Mujahideen and their formation in the arts of fighting and revolutionary war. Its importance stands out in that it is one of the main tasks that the leaders of the revolution focused on to achieve a set of goals, and it is considered one of the factors that contributed to the victory of the National Liberation Army. The leadership of the revolution opened several military training centers, including the Beja Military Training School in 1956 on the Tunisian-Algerian border, to train the elements of the Liberation Army as the first Algerian training school during the liberation revolution, under the supervision of Rabah Idir as an official at the center assisted by Algerian trainers after they piled up in the Arab Mashreq, where they worked on Develop a rich, intense and rich program in the military and martial arts, based mainly on guerrilla warfare as a strategy in the face of the French army.